Ni36.67Co30Fe16.67Ti16.67 30% engineering strain - Nöhring, Wolfram G.; Hinkle, Adam R.; Pastewka, Lars (contact.engineering, 2020)
This surface is the result of a Molecular Dynamics simulation of bi-axial compression of a single crystal Ni36.67Co30Fe16.67Ti16.67 solid solution. The initial configuration was a Ni36.67Co30Fe16.67Ti16.67 cube with side length 100 nm. The x- and y-directions of the simulation cell were parallel to the [-34-1] and [-5-27] directions of the crystal, respectively. The z-direction was parallel to the [111] crystal direction. The x- and y-directions were periodic, but the z-direction was free, hence the crystal had free surfaces along z. The present surface is the free surface in positive z-direction. The surface was initially an atomically flat (111) facet, but roughened by plastic deformation.

The crystal was deformed with a rate of 1e8 s^-1 at a temperature of 100K. The temperature was controlled using a Dissipative Particle Dynamics thermostat.
This dataset contains the surface at 30% engineering strain (side length ca. 70.1 nm).

The simulations have been reported in the following publication:

Hinkle, A. R.; Nöhring, W. G.; Leute, R.; Junge, T.; Pastewka, L. The Emergence of Small-Scale Self-Affine Surface Roughness from Deformation. Science Advances 2020, 6 (7), eaax0847. https://doi.org/10.1126/sciadv.aax0847.

See this publication for additional information.
Keywords: FOS: Materials engineering